Testing Different Message Styles about Unnecessary Antibiotics Using an Online Platform - Stenlund, Säde; Appelt, Kirstin C.; Ruby, Matthew B.; Smith, Nick; Lishman, Hannah; Patrick, David M. (MPDI, 2025)
Patients' expectations are a major contributor to the unnecessary prescribing of antibiotics, yet limited research has examined how physicians can calibrate these expectations. The studies we conducted tested how varying messages could impact patients' expectations for antibiotics and their experience of medical appointments. All the participants read a short scenario about an appointment for mild sinusitis symptoms, with the patient's expectation of antibiotics. In Study 1, the participants (n = 1069) were randomly assigned to read a positively framed, neutral, or negatively framed message regarding unnecessary antibiotics. In Study 2, the participants (n = 1073) read a message emphasizing either the societal or personal harms of unnecessary antibiotics, or a message without additional rationale. None of our pre-registered hypotheses were supported, but our exploratory analyses indicated that the societal message increased concern about antibiotic resistance. The participants who were more concerned about resistance were less likely to ask for antibiotics, more satisfied when the physician did not prescribe them, and more likely to recommend the physician to a friend. Discussing the consequences of the different courses of action did not appear to negatively impact physician-patient rapport. These studies demonstrate an inexpensive method with which to pre-test various messages about antibiotic consumption, and suggest that such messages are not negatively received by patients.